Electrodeposition of Co-Ni-Fe on Stainless Steel Bolts - S. Md.Nor, M.; Salleh, Z.; R. N. M. Masdek, N.; M Taib, Y.; Z. Abu, M. (International Journal of Engineering and Technology, 2018)
In a fastening system, bolt is the first component to be susceptible to corrosive attack. The focus of the study is to investigate the feasibility of coating stainless steel 304 bolts and the coating properties obtained. In this study, the bolts were coated with cobalt-nickel-iron (Co-Ni-Fe) alloy through electrodeposition using platinized titanium as the anodes. The temperature used was 50Â°C and the pH of the sulphate solution were 2. The current density was 96.68 mA/cm2 and deposition time was 30 minutes. The optimum electrodeposition parameters were studied through trial and error. The characteristics of coating such as elemental percentage and microhardness were compared with the substrate. The optimum parameters obtained were current density of 145.01 mA/cm2, temperature of 60Â°C and 30 minutes of deposition time. The suitable substrate orientation was horizontally hanged and rotated 60Â° around screw axis for every 5 minutes. The mean thickness of coating was 117.4 Âµm. The coating exhibited 25% hardness improvement over the substrate. The 2 litres solution could be used for 7.5 hours (15 plating cycles) to produce 15 samples. As a conclusion the surface hardness was not compromised despite that Co-Ni-Fe ions had depleted in the solution.Â